Autonomy and entrepreneurial intention among college students - Cholichul Hadi, Yanti Amalia, (Opción, 2020)
This study aimed to determine the relationship between independence and entrepreneurial intention in students via the data collection approach or method in the form of a survey. The variables studied were entrepreneurial intentions and independence. As a result, the independent variable had a relationship classified as weak with entrepreneurial intention variables. In conclusion, there was no significant relationship between independence and entrepreneurial intentions in which independence was more influential and had a strong relationship with individual characteristics, such as self-efficacy, need for achievement, and need of independence—which were considered as identical traits of entrepreneurs.